Capsule endoscopy in diagnosis of small bowel diseases: a health technology assessment. Issue 2 (May 2014) - Li, Xiang Lian; Shen, Jian Tong; Li, You Ping; Tang, Cheng Wei; Huang, Li Bin; Li, Cui Cui; Yu, Jia Jie; Wang, Ying Jiang; Yang, Zong Xia
Abstract Objectives Capsule endoscopy (CE) has been widely used in the diagnosis of small bowel disease (SBD) in the world. To bring CE into the national health insurance directory, and intensify its popularization in primary hospital, the government needs high‐quality HTA evidence for decision makers. We were appointed by the National Health and Family Planning Commission of China to evaluate the effectiveness, safety, economy, and applicability of CE in the diagnosis of SBD, to provide the best currently available evidence for decision making. Methods We searched the Cochrane Library (Issue 8, 2013), PubMed, EMbase, INAHTA, VIP, CBM, CNKI and WanFang Data. All confirmed or suspected SBD patients with diagnosis by CE versus other alternative therapies were considered. Health technology assessments (HTAs), systematic reviews (SRs), meta‐analyses, randomized controlled trials (RCTs), guidelines and economic studies were included. Two investigators selected studies, assessed the quality and extracted data independently, and a descriptive analysis was used. Results We included 4 HTAs, 11 SRs/meta‐analyses, 2 RCTs, 5 guidelines, and 10 economic studies for assessment. The results showed that the disease detection rate of CE was higher than that of many other traditional technologies and that the main adverse event for CE was retention (0.7% to 3.0%). These results were consistent with those of the guidelines. Comprehensive results of economic studies showed the superiority of CE compared with other technologies. As the first choice, CE can decrease potential costs, especially when used in outpatients. Conclusions (i) CE has advantages in diagnostic yield, safety, and cost in the diagnosis of SBD, but some limitations exist. It still needs more high‐quality evidence on CE diagnosis accuracy. (ii) When the government approves the introduction of CE in a hospital, many factors must be considered, such as the local disease burden, clinical demand, ability to pay, and staff. At the same time, it is necessary to standardize training for operating physicians, to reduce economic losses caused by poor technical ability of the medical staff.